2003
DOI: 10.1093/ndt/gfg272
|View full text |Cite
|
Sign up to set email alerts
|

Optimal anticoagulation strategy in haemodialysis with heparin-coated polyacrylonitrile membrane

Abstract: During the rinsing phase, the ionic interactions between the new AN69ST polyacrylonitrile membrane and unfractionated heparin induce stable heparin coating. This allows a significant reduction of systemic anticoagulant requirements without increasing the risk of clotting, both in the experimental setting and in the chronic haemodialysis patients. Further studies are required to assess this advantage in patients with acute renal failure and at risk of bleeding and to reduce the metabolic consequences of long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 19 publications
0
60
1
1
Order By: Relevance
“…Hauen erabilera biomedikuntzan ugaria da: besteak beste, poliuretanozko bihotz artifizialak [5,6], poliakrilonitrilozko dialisirako mintzak [7], edo polimetilmetakrilatozko ukipen lenteak [8].…”
Section: Sarreraunclassified
“…Hauen erabilera biomedikuntzan ugaria da: besteak beste, poliuretanozko bihotz artifizialak [5,6], poliakrilonitrilozko dialisirako mintzak [7], edo polimetilmetakrilatozko ukipen lenteak [8].…”
Section: Sarreraunclassified
“…Zhu et al [6], Jiang et al [7] and Huang et al [8,9] also improved blood compatibilities of the poly(vinylidene fluoride), polyethylene (PE) and PSF membranes by covalent attachment of heparin [6][7][8][9]. In vivo tests carried out with commercial hemodialysis membranes, AN69 ST, HEMOPHAN and EVODIAL showed that it is possible to reduce systemic administration of heparin through its immobilization on these membranes [10][11][12][13][14][15]. On the other hand, one clinical study reported that heparin coated AN69 ST membrane does not reduce clotting during hemodialysis when compared to a conventional PSF filter [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used approach is to mimic endothelial cell layer by heparin immobilization. The beneficiary effect of heparin coatings on the membranes has been reported by many authors both in vitro [1][2][3][4][5][6][7][8][9] and in vivo [10][11][12][13][14][15]. For example, Cheung et al [1] observed that complement activation induced by hemodialysis can be modulated with heparin immobilized cellulose acetate membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of the polyacrylonitrile membrane AN69 dialyzer is strongly electronegative, but pretreating the AN69 filter with polyethyleneimine reduces its surface electronegativity and allows heparin to bind more firmly [2,3,4]. An increased frequency of hypersensitivity reactions has previously been reported during HD with the electronegatively charged AN69 filter in patients treated with angiotensin-converting enzyme inhibitors (ACEI) [5].…”
Section: Introductionmentioning
confidence: 99%